OPERATIONAL RESTRICTIONS FOR REDUCING NOISE AND THE SAFETY OF AIR OPERATIONS - Anna KWASIBORSKA; Jacek SKORUPSKI (Scientific Journal of Silesian University of Technology. Series Transport)
Many European airports are located in close proximity to residential or protected areas. Aircraft noise emissions caused by the landing and taking off of aircraft are a big problem in these areas. From an operational point of view, the method for reducing noise is to reduce traffic volume or change its organization, especially during the night. Some procedures and tools have been developed to support air traffic management in the implementation of operational constraints necessary to maintain noise at an acceptable level. The objective of this paper is to analyse the effectiveness of these tools. For this purpose, we have analysed existing methods of operational noise reduction, taking into account their influence on the structure, smoothness, punctuality and, especially, the safety of air traffic. As a result, existing risks have been identified, while methods have been proposed to combine two important air traffic service tasks: ensuring safety, while taking into account the environmental constraints, especially in relation to the acoustic climate.